Barack Obama's family tree : roots of achievement - Zumbusch, Amelie von. (New York, NY : PowerKids Press, 2010)
This book takes a look at the fascinating and diverse family history of Barack Obama. Readers will learn about his Kansas-born mother and his father who was from Kenya. Theyll learn about the influence that his parents had on his life, as well as the influence of his paternal and maternal grandparents. Students will come away with the understanding that challenges, separation, and loss can be translated into success and achievement, all depending upon how an individual chooses to approach adversity.
A strong family -- Barack Obama's family tree -- Born in beautiful Hawaii -- A lively grandfather -- A practical grandmother -- Smart with a kind heart -- Roots in Kenya -- The father of eight children -- Visiting Kenya -- The Obamas' future.
Includes index.
Keywords: Obama, Barack -- Family -- Juvenile literature; Presidents -- United States -- Family -- Juvenile literature; Obama, Barack -- Family; Presidents -- United States -- Family